Miss Hogos' Korean Food Truck / Ain Izzati Badrol Sham ... [et al.] - Badrol Sham, Ain Izzati; Muhammad Asikin, Amelia Habeebah; Zambri, Amira Sofea; Fei, Anith Laila; Mohd Yusri, Atiqah Najiyah; Pit, Nur Hafifie (2016)
MISS HOGOs' is an original, local company responsible for introducing Korean street food from Korea to streets of Malaysia. Due to the arising of Korean trend in Malaysia where there are many Korean cuisines based restaurants are open and gaining attention, we decided to venture into the arising Korean food competition.